El proceso de enseñanza aprendizaje en la compresión lectora de los estudiantes de sexto año de educación básica en la unidad educativa la Maná - Masapanta Masapanta, Jessica Fabiola (2021)
The present research refers to: The teaching-learning process in the reading comprehension of students in the sixth year of Basic Education in La Maná Unit in the period 2021/2022. The importance of the research lies in the fact that it addresses a significant issue that we are currently experiencing, the use of techniques for reading comprehension, since it is a fundamental point to express ourselves to other people and to have good communication skills. Understanding what is read is the important part to acquire new knowledge. The main objective of the research is to elaborate innovative didactic strategies that allow the improvement of reading comprehension and development of communicative skills in the students of the sixth year of Basic Education of the Educational Unit La Maná. The research will work with a qualitative and quantitative approach; where the survey technique was applied to the 42 students with the structured questionnaire instrument divided into three parts: global, detailed and selective comprehension, using the Google forms program in which it can be evidenced that the group of students have a low level of reading comprehension, since the average is below the normal average. Finally, the conclusions of the research determine that it is important to use reading comprehension techniques, to analyze the communicative skills of the students and to disseminate the results to the university community in order to strengthen the area of Language and Literature